2002
DOI: 10.1152/ajpcell.00359.2001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a voltage-dependent Na+current in human esophageal smooth muscle

Abstract: Smooth muscle contraction is critical to peristalsis in the human esophagus, yet the nature of the channels mediating excitation remains to be elucidated. The objective of this study was to characterize the inward currents in human esophageal smooth muscle cells (HESMCs). Esophageal tissue was isolated from patients undergoing surgery for cancer and grown in primary culture, and currents were recorded using patch-clamp electrophysiology. Depolarization elicited inward current activating positive to −40 mV and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…This study using cultured hASMCs has shown the expression of the SCN9A ␣-and ␤ 1 -subunit. The expression of SCN9A in smooth muscle cells has been previously described in human cultured bronchial, coronary, and pulmonary arterial smooth muscle cells (3,17) and differs from human esophageal smooth muscle cells, which express SCN4A and -5A (9,17). The protein expression of Na V 1.7 encoded by SCN9A was further verified by immunocytochemistry.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…This study using cultured hASMCs has shown the expression of the SCN9A ␣-and ␤ 1 -subunit. The expression of SCN9A in smooth muscle cells has been previously described in human cultured bronchial, coronary, and pulmonary arterial smooth muscle cells (3,17) and differs from human esophageal smooth muscle cells, which express SCN4A and -5A (9,17). The protein expression of Na V 1.7 encoded by SCN9A was further verified by immunocytochemistry.…”
Section: Discussionmentioning
confidence: 65%
“…However, it is different from that in the human heart (13) and esophageal smooth muscle cells where I Na is TTX insensitive (9).…”
Section: Discussionmentioning
confidence: 70%
“…Evidence has shown that, in vascular smooth muscle, action potentials are not dependent on Na + channels since tetrodotoxin (TTX) has no effect on amplitude and duration of action potentials [18], leading to the belief that these channels might not be present or prominent in these tissues. Nonetheless, Na + currents (I Na ) have been measured in visceral smooth muscles such as myometrium and uterus (pregnant), colon, esophagus, stomach, and ureter as well as in certain vascular smooth muscles such as the portal and azygos veins [2,8,[24][25][26]31,33,34]. The identification of functional voltage-gated Na + channels in quiescent and proliferating vascular smooth muscle cells (VSMC), however, has not been as forthcoming.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 11 known pore-forming α subunit (SCN-A) genes, only five (i.e. SCN3A, SCN4A, SCN5A, SCN6A, and SCN7A) have currently been identified in smooth muscle cells, while all or most are expressed in brain tissues, skeletal muscle, or cardiac myocytes [8,13,15]. In vascular tissues, the list has been further narrowed down to SCN5A, SCN6A, and SCN7A, which all represent TTX-resistant Na + channel isoforms [21].…”
mentioning
confidence: 99%
“…Several Na + influx pathways may be involved in setting RMP in LES muscle and could include selective Na + channels, non-selective cation channels, Na + /K + pumps, and Na + -Ca 2+ exchangers. A voltage-activated Na + channel has only been demonstrated in cultured esophageal smooth muscle cells (Deshpande et al 2002). Non-selective cation channels are readily demonstrated in many gut smooth muscles (Sims 1992) and have been implicated in setting the level of RMP and in voltage and ACh-stimulated Ca 2+ influx.…”
Section: Resting Membrane Potentialmentioning
confidence: 99%